ALOKASI PENGELUARAN DAN TINGKAT KESEJAHTERAAN KELUARGA PADA KELUARGA NELAYAN BAGAN - Widyaningsih, Erni; Muflikhati, Istiqlaliyah (Department of Family and Consumer Sciences, Faculty of Human Ecology, IPB University, 2015)
This research aimed to analyze family expenditure allocation and welfare of bagan fishermen. Research conducted in Sarang Tiung Village, Pulau Laut Utara Subdistrict, Kotabaru. This research involved 50 families who have a bagan consisting of 50 husbands and 50 wives selected by simple random sampling method. Data was collected by interview with wife and husband using questionnaire. Variables measured include of characteristics the family, expenditure allocation, and family welfare of bagan fishermen. Data was analyzed using descriptive, correlation test, independent sample t-test, and multiple linier regression test. The result showed a greater proportion of food expenditure (61,06%) than nonfood expenditures (38,94%). Most of bagan fisherman families are classified as nonpoor by objective welfare indicator. Husband well-being is higher than wife, especially in physical-economy dimension. There are significant difference between subjective well-being husband and wife with p<0,001. Subjective well-being the husband influenced by family size, health, and communication spending. Subjective well-being the wife influenced by amount of bagan, communication, and social activities spending.